Hina Jilani on her Satyagraha for Women's Rights in Pakistan. Issue 2 (December 2016) - Kakoty, Juanita
This piece is based on a conversation the author had with lawyer and human rights activist from Pakistan, Hina Jilani, in May 2016. It captures Jilani's account of the 'Satyagraha' she has waged in her lifetime for the rights of women in her country; and as she narrates her story, she interweaves it with the 'Satyagraha' that shaped the women's movement in Pakistan. One can read here about Jilani's struggle for truth, for a human rights consciousness in a political climate of military regime; and how she challenged courts in the country to step outside the realm of conventional law and extend justice to women and girls. And in the process, learn that her struggle for truth has been intertwined with that of the women's movement in the country.